2020
DOI: 10.1159/000510625
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Denosumab for Life-Threatening Hypercalcemia in a Pediatric Patient with Primary Hyperparathyroidism

Abstract: <b><i>Introduction:</i></b> Primary hyperparathyroidism (PHPT) is rare and usually symptomatic in children. There is no approved medication to lower serum calcium levels in this patient group. Denosumab is used in adult patients with osteoporosis and hyperparathyroidism. To our knowledge, only 1 case of denosumab treatment in a child with severe PHPT has been reported to date. <b><i>Case Presentation:</i></b> A 16-year-old female was referred to our clinic with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Another patient (case 6) underwent surgery 22 days after admission. This case had family history of PHPT, and hence genetic testing was performed before surgery ( 8 ). Emergency surgeries after initial treatment might be imperative because a hypercalcemic crisis can result in fatal consequences in cases where prompt and proper treatment cannot be provided, and surgery is the only curative treatment for PHPT ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another patient (case 6) underwent surgery 22 days after admission. This case had family history of PHPT, and hence genetic testing was performed before surgery ( 8 ). Emergency surgeries after initial treatment might be imperative because a hypercalcemic crisis can result in fatal consequences in cases where prompt and proper treatment cannot be provided, and surgery is the only curative treatment for PHPT ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…HPT-JT is another hereditary disease that can present with PHPT in pediatric patients. Among seven cases of hypercalcemic crisis in pediatric patients shown in Table 1 , one case (case 6) was diagnosed as HPT-JT, as evidenced by a pathogenic mutation in CDC73 ( 8 ). A single parathyroid tumor is usually responsible for the development of PHPT in patients with HPT-JT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases where denosumab was used to manage hypercalcemia in PHPT, it was administered subcutaneously at a reduced dose of 60 mg. It has been reported that after a single dose, serum calcium levels begin lowering after 12 hours with normalization in three days (8)(9)(10)(11)(12). We also used a single dose of denosumab (60 mg), and calcium levels begun lowering after 12-24 hours.…”
Section: Discussionmentioning
confidence: 99%